(727) Some General Remarks on The Successive Stages Method in Planning with an random Consideration of the Time Lag Effects on the Economy's Development بعض الملاحظات العامة حول طريقة المراحل المتعاقبة في التخطيط مع اعتبار عشوائي لتأثيرات تأخير الوقت على تنمية الاقتصاد - sadek, Yousry (INP, 2024)
This text discusses the concept of planning in stages and the impact of introducing the concept of time lag, particularly in the case of an expanding economy. The author does not engage in a discussion of the advantages and disadvantages of the method of national planning in stages in this brief paper, but mentions that this will be addressed in detail in their forthcoming research work titled "National Planning in Stages Versus Simultaneous National Planning. “The method of planning in stages (two stages or more) mainly consists of choosing total production and total investment in the first stage, viewed as aggregates for the years defined in the program or plan. In the second stage, the composition of production for each year is selected separately. The first stage aims to determine the future course of production by selecting an optimal investment program. One principle upon which an optimal investment program may rest is the maximization of utility over time, along with the maximization of justice between present and future generations. In the second stage, the choice of the composition of production for a year or specific time period can be made, with some economists arguing that this choice should be based on the principle of maximizing national income growth at world market prices, considering the given volume of investment resulting from stage one.